Screening of bacterial contamination on shopping trolley handles from supermarkets in Kuala Pilah / Saidatul Ashikin Mohd Asri - Mohd Asri, Saidatul Ashikin (2018)
Shopping trolleys are used by the public in every supermarket worldwide. It is used by people from various backgrounds, especially in terms of jobs and personal hygiene practice which may lead to the transferring of bacteria from users’ hand to the handle or the other way round. The aims of this study were to isolate and screen Escherichia coli, Staphylococcus aureus and Salmonella spp. on shopping trolley handles from two different supermarkets in Kuala Pilah. Samples were cultivated on selective media and further characterization was done through Gram staining and biochemical tests such as Indole, methyl-red, Voges-Proskauer and citrate test. The results of this study showed that none of the three aforementioned bacteria were isolated, and the isolates from samples taken from the supermarkets harbored Citrobacter sp. and two unidentified bacteria, of Gram-positive and Gram-negative bacteria. The detection of Citrobacter sp. and possible colonization of S. aureus suggest that there are contamination of disease-causing bacteria on shopping trolley handles that calls for good hygiene practice.